Association between daytime napping and cognitive impairment among Chinese older population: a cross-sectional study - Hong Zhang; Lijuan Zhang; Chen Chen; Xiaoni Zhong (Komiyama Printing Co. Ltd, 2023)
Background: Both napping and nighttime sleep duration have been reported to be associated with cognitive function in older adults, whereas little is known about the association between daytime napping and cognitive impairment in different nighttime sleep duration subgroups. This study aimed to explore the correlation between daytime napping and cognitive impairment across nighttime sleep duration subgroups. Methods: A cross-sectional study was conducted by using the fourth survey of China Health and Retirement Longitudinal Study (CHARLS). We utilized the Mini-Mental State Examination (MMSE) scale to define cognitive impairment, and the daytime napping and nighttime sleep duration was self-reported by individuals. We applied the Restricted Cubic Spline (RCS) to analysis the dose-response relationships between daytime napping and cognitive impairment. And the multivariate Logistic Regression Model (LRM) was performed to evaluate the association of daytime napping and cognitive impairment. Results: A total of 3,052 individuals were included, of which 769 were cognitive impairment. The RCS showed there were non-linear association between daytime napping and cognitive impairment in all participants group and longer nighttime sleep duration subgroup (PNon-linear < 0.05, PDaytime napping < 0.05). The LRM revealed no napping (OR = 1.62, 95%CI 1.14-2.30) and excessive napping (1.64 95%CI 1.09-2.48) were related to cognitive impairment in longer nighttime sleep duration subgroup. Conclusions: Daytime napping had nonlinear association with cognitive impairment in Chinese elderly population. No napping and excessive daytime napping (>90 minutes) were related to cognitive impairment in participants with 7 and more hours nighttime sleep duration.